Quantitative analysis of the V838 Monocerotis spectrum - Kaminsky, B.; Pavlenko, Ya.V. (Кинематика и физика небесных тел, 2005)
We present the determination of the effective temperature, iron abundance, and microturbulent velocities for the pseudophotosphere of V838 Mon observed on February 25, March 2 and 26, 2002. Physical parameters of the line forming region were obtained in the framework of a self-consistent approach using fits of synthetic spectra to observed spectra in the wavelength range 5500–6700 Å. We obtained the values of Teff 5330±150 K, 5540±150 K, and 4960±150 K for February 25, March 2, and March 26, 2002, respectively. The iron abundance logN(Fe) = −4.7 does not appear to change in the atmosphere of V838 Mon from February 25 to March 26, 2002.